Studi Aktivitas Antioksidan Hasil Fermentasi Kopi Arabika (Coffea arabica L.) Dan Andaliman (Zanthoxylum acanthopodium DC.) - Yessi Febriani; Salman Salman; Dewi Lestari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Arabica coffee (Coffea arabica L.) and andaliman (Zanthoxylum acanthopodium DC.) are recognized as sources of bioactive compounds, particularly phenolic and flavonoid compounds, which have potential antioxidant activity. Fermentation processes may improve the bioactive components of coffee, while the addition of andaliman may enhance its antioxidant potential. However, information regarding the antioxidant activity of fermented Arabica coffee combined with andaliman in various formulations remains limited. Objective: This study aimed to analyze the phytochemical characteristics and antioxidant activity of fermented Arabica coffee with the addition of andaliman in various formulations using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Methods: An experimental study was conducted using six formulations consisting of F0 (control), F1, F2, F3, F4, and F5 with different amounts of andaliman addition. Phytochemical screening was performed to identify secondary metabolites. Antioxidant activity was evaluated using the DPPH method at sample concentrations ranging from 5 to 25 ppm, while vitamin C was used as a positive control at concentrations of 0.3–0.7 ppm. The sample and DPPH solution were incubated for 30 minutes in a dark condition, and absorbance was measured using a UV-Vis spectrophotometer. The percentage of inhibition and IC₅₀ values were calculated using linear regression analysis. Results: Phytochemical screening showed the presence of alkaloids, flavonoids, tannins, saponins, and phenolic compounds in fermented Arabica coffee with andaliman addition. Antioxidant evaluation demonstrated that all formulations exhibited very strong antioxidant activity. The IC₅₀ values obtained were 28.09 µg/mL for F0, 26.90 µg/mL for F1, 22.10 µg/mL for F2, 17.49 µg/mL for F3, 21.79 µg/mL for F4, and 23.71 µg/mL for F5, while vitamin C showed an IC₅₀ value of 0.08 µg/mL. Formula F3 exhibited the highest antioxidant activity, indicated by the lowest IC₅₀ value among all formulations. Conclusion: Fermentation of Arabica coffee with the addition of andaliman produced very strong antioxidant activity. Formula F3 was identified as the optimal formulation and has potential to be developed as a functional beverage based on local ingredients. Further studies regarding product stability and in vivo antioxidant activity are recommended.